2002
DOI: 10.1525/si.2002.25.4.463
|View full text |Cite
|
Sign up to set email alerts
|

Bad Girls and Fallen Women: Chronic STD Diagnoses as Gateways to Tribal Stigma

Abstract: This article uses women's firsthand experiences as the basis from which to explore how social constructions of sexual disease and feminine morality merge to threaten women's sexual selves during sexually transmitted disease (STD) diagnostic interactions. Constant comparative analysis of interview data reveals how forty‐three women made sense of this stage in their moral careers. Adding to interactionist literature on gender and chronic illness, this article expands discussions of tribal stigma to the intrapers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 38 publications
2
48
1
Order By: Relevance
“…These findings do not support results from the study conducted by Nack (2002), who found that women with herpes and HPV who were in committed relationships reported that they felt that being in a relationship somehow buffered them from the stigma of having an STI and eased the shock of their STI diagnosis.…”
Section: Effects Of Sti Statuscontrasting
confidence: 93%
See 1 more Smart Citation
“…These findings do not support results from the study conducted by Nack (2002), who found that women with herpes and HPV who were in committed relationships reported that they felt that being in a relationship somehow buffered them from the stigma of having an STI and eased the shock of their STI diagnosis.…”
Section: Effects Of Sti Statuscontrasting
confidence: 93%
“…This may cause great distress for the infected individual. Nack (2002) found that relationship status appeared to affect how women with genital herpes or HPV or both handled their diagnosis. Women with genital herpes and HPV who were in committed relationships reported that being in a relationship buffered them from the shame and stigma of having an STI.…”
Section: Danielle C Newton and Marita Mccabementioning
confidence: 99%
“…Stigma is a socially constructed concept and, according to Goffman's (1963) foundational work on the subject, can be associated with physical attributes (e.g., a sexually transmitted infection), moral attributes (e.g., engaging in risky behaviour) or 'tribal' affiliation. Nack (2002) extends this concept of tribe beyond familial/ethnic associations in the context of sexual behaviour norms attributed to a particular group. Young people represent a socially distinct group, and an understanding of their own identities as sexual beings is informed by many of the morals that are entrenched in negative social constructs of young people's sexuality (e.g., stigmatisation of certain sexual behaviours as 'risky' or immoral).…”
Section: Discussionmentioning
confidence: 94%
“…The study by Nack quoted above argued for generalisability of the findings by drawing on Goffman's analysis of stigma but also on the well-researched theoretical concept of a 'career', involving re-definition of identity as a result of illness or trauma. 40 Thus, confidence in the generalisability of the findings grows.…”
Section: Drawing Research Conclusionmentioning
confidence: 97%
“…40 She drew on feminism and Goffman's analysis of stigma to structure a study of the way in which women's sexual self is transformed by diagnosis of an STD. She disclosed her own STD status.…”
Section: An Examplementioning
confidence: 99%